Mapping the Role of Female Farm Workers in Family Economic Security: A Bibliometric and Systematic Literature Review - Elfi Sahara; Muchlis Bahar; Duhriah Duhriah (Turast: Jurnal Penelitian dan Pengabdian, 2025)
This research aims to carry out mapping and bibliometric analysis as well as systematic literature reflection (SLR) related to the role of family economic security. Quantitative and qualitative approaches were used using Google Scholar with the time period 2013-2023 with the keyword family economic resilience. The results of the bibliometric analysis show that trends in family economic security have waxed and waned over time. The highest publication occurred in 2022 with a total of 16 articles published. Meanwhile, the lowest publication occurred in 2016 with 3 articles. SLR findings identify that female agricultural workers have been able to meet the indicators of family economic resilience. Based on the results of the analysis, it can be concluded that the influence of female agricultural workers on the economic resilience of the family has a very positive influence on the economic resilience of the farming family.